Realisation of polyester fabrics with low transmission for ultraviolet light. (26th March 2020) - Hoque, Mohammad Toufiqul; Mahltig, Boris
Abstract: Due to the hazardous impact of ultraviolet (UV) light, textiles with UV‐protective properties are in great demand. This paper is related to the equipment of polyester textiles, with three different organic and water‐insoluble UV absorbers containing a cinnamate basic structure. To apply the UV absorbers from water‐based recipes, they are combined with polyethylene glycol PEG200 and different dispersing agents. The application onto two different polyester textiles is performed with a conventional high temperature process driven at 130°C with a process duration of more than 1 hour. Alternatively, an innovative microwave‐assisted process of a shorter duration of only 15 minutes is performed at 130°C. This microwave process is performed under solvothermal conditions using a CEM discover microwave machine. The sample evaluation is performed by UV‐visible spectroscopy in an arrangement of diffusive transmission with a special view of the spectral region from 300 to 500 nm. Finally, polyester fabrics with enhanced UV‐protective properties are realised. It is possible to decrease the diffusive transmission for the complete range of UV light to values of smaller than 5%. By contrast, the influence on the interaction with visible light is low, so the coloration properties of the treated polyester fabrics are less affected. The developed process can be used to realise polyester fabrics for various UV‐protective applications by a simple approach. The developed microwave process allows a decrease in process duration to more than 75% compared with the analogously presented high temperature process.